Optical methods used to optimise semiconductor laser structures with tunnel injection from quantum well to InGaAs/GaAs quantum dots - Rudno-Rudziński, Wojciech; Ryczko, Krzysztof; Sęk, Grzegorz; Syperek, Marcin; Misiewicz, Jan; Pavelescu, Emil-Mihai; Gilfert, Christian; Reithmaier, Johann Peter (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
We present the results of optical measurements performed on structures consisting of an InGaAs quantum well (QW), separated by a thin barrier from a layer of self-assembled InGaAs quantum dots (QDs). Such a kind of design is called a tunnel injection structure, because its functionality is based on the tunnelling of carriers from a QW to QDs, preferably with the assistance of optical phonons. In this approach, the injector QW serves as a reservoir of the carriers (due to much higher efficiency of carrier collection) and alleviates the problem of long relaxation times needed for carriers to reach the QDs ground state. In order to investigate the structures several complementary experimental techniques are applied. Photoreflectance, an absorption-like modulation spectroscopy, gives the information about the optical transitions and the electronic structure. The temperature evolution of photoluminescence allows emission efficiency and carrier losses to be determined. Photoluminescence excitation probes directly the carrier transfer from QW to the dots. The interpretation of the results is supported by the calculations in the envelope function formalism. It has been found out that the wavefunction position of the lowest lying levels depends on the QW parameters and thus different regimes of tunnelling are proposed.
Optica Applicata, Vol. 39, 2009, nr 4, s. 923-932
Keywords: optyka; quantum dots; optical properties; lasers; tunnel injection